Franklin and the baby - Moore, Eva.; Bourgeois, Paulette; Clark, Brenda; Nelvana (Firm) (New York : Scholastic, 1999)
Franklin befriends a baby bear.
"Based on the characters created by Paulette Bourgeois and Brenda Clark."
3.0
K-3
K-3
Keywords: Turtles -- Fiction; Bears -- Fiction; Animals -- Fiction; Turtles -- Fiction; Bears -- Fiction; Animals -- Fiction